SnO/SnO2 heterojunction: an alternative candidate for sensing NO2 with fast response at room temperature - Wang, Pengtao; Ge, Wanyin; Jia, Xiaohua; Huang, Jingtao; Zhang, Xinmeng; Lu, Jing (Frontiers of materials science, 2022)
The SnO 2 -based family is a traditional but important gas-sensitive material. However, the requirement for high working temperature limits its practical application. Much work has been done to explore ways to improve its gas-sensing performance at room temperature (RT). For this report, SnO 2 , SnO, and SnO/SnO 2 heterojunction was successfully synthesized by a facile hydrothermal combined with subsequent calcination. Pure SnO 2 requires a high operating temperature (145 °C), while SnO/SnO 2 heterojunction exhibits an excellent performance for sensing NO 2 at RT. Moreover, SnO/SnO 2 exhibits a fast response, of 32 s, to 50 ppm NO 2 at RT (27 °C), which is much faster than that of SnO (139 s). The superior sensing properties of SnO/SnO 2 heterojunction are attributed to the unique hierarchical structures, large number of adsorption sites, and enhanced electron transport. Our results show that SnO/SnO 2 heterojunction can be used as a promising high-performance NO 2 sensitive material at RT.